2015
DOI: 10.1021/acs.cgd.5b00126
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth Rate Dispersion versus Size-Dependent Crystal Growth: Appropriate Modeling for Crystallization Processes

Abstract: Crystal growth rate dispersion (GRD) and size-dependent crystal growth (SDG) models are models to extend McCabe's ΔL Law to more accurately account for variation in the crystal growth rates within a population of crystals. GRD is a phenomenon where the crystal growth rate either fluctuates randomly over time or varies over a population of crystals. SDG is where the growth rate of a crystal depends on its size, typically with growth rates assumed to increase monotonically with crystal size. Although it has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…Because individual grains in the same sample should have different interface conditions for interface‐controlled kinetics or different effective diffusivities around growing grains, the stochastic dispersion of the kinetic constant is reasonable for natural samples. Indeed, a growth rate dispersion depending on the surface condition of growing grains in the solution has been proposed as a real phenomenon (Srisanga et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because individual grains in the same sample should have different interface conditions for interface‐controlled kinetics or different effective diffusivities around growing grains, the stochastic dispersion of the kinetic constant is reasonable for natural samples. Indeed, a growth rate dispersion depending on the surface condition of growing grains in the solution has been proposed as a real phenomenon (Srisanga et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The dashed line has a slope of one grains, the stochastic dispersion of the kinetic constant is reasonable for natural samples. Indeed, a growth rate dispersion depending on the surface condition of growing grains in the solution has been proposed as a real phenomenon (Srisanga et al, 2015).…”
Section: Discrimination Of the Growth Kinetics Of Metamorphic Zirconmentioning
confidence: 99%
“…Size‐dependent growth (SDG) is also used to explain deviations from McCabe's Δ L law of crystal growth. However, recent work suggests that SDG is not a real phenomenon except for crystals small enough that their solubility is different to the bulk crystal phase 3 and so it is not considered here.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that crystal growth rate kinetics may display several unusual features, such as size‐dependent crystal growth , , crystal growth rate dispersion , or dead zones where no growth occurs , . However, most measurements of kinetics reported have considered only average growth rates and have been fitted with a simple power law model that cannot account for these unusual features.…”
Section: Introductionmentioning
confidence: 99%
“…There are three mechanisms used to explain, and therefore, model growth rate dispersion: the intrinsic crystal growth model , the random fluctuation model , and the common history model . Recently, it was shown that size‐dependent crystal growth was typically a manifestation of crystal growth rate dispersion , for which cause and effect have not been adequately determined, except for very small particles, less than about 1 μm, that may have a different thermodynamic stability to that of larger crystals. Crystal growth rate dispersion is normally modeled by using a specific crystal growth rate model with a probability distribution, f ( k g ) 1) , which represents the crystal growth rate constant , as shown in Eq.…”
Section: Introductionmentioning
confidence: 99%